The costs and benefits of host feeding in parasitoids - Rivero, A; West, SA (2005)
Parasitoids are ideal organisms for testing theories concerning the trade-off between current and future reproduction. Upon encountering a host, a female has to decide whether to lay an egg, and thus invest in her current reproduction, or feed on the host to invest in her future reproduction. Theory predicts that the optimal female decision will depend on the costs and benefits of host feeding. The benefits of host feeding are well understood, but there is a lack of data on the associated costs. Models developed so far have assumed costs to be fixed: a host used for feeding cannot be used for egg laying and thus represents zero returns in terms of future reproduction. We investigated the costs and benefits of host feeding in Nasonia vitripennis, one of the many parasitoid species that can feed and lay eggs on the same host. Host feeding increased egg production but had no effect on the longevity of females; it also reduced the fitness of female offspring by significantly decreasing their size at emergence (no equivalent effect was found in male offspring). Female offspring size was negatively correlated with the extent of host feeding that had taken place in the host from which they emerged. The costs of host feeding in this species are therefore not fixed but vary according to the amount of nutrients extracted from the host. © 2005 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.